Dental caries and visual acuity of students in a town in west amazon - Lauramaris de Arruda Régis-Aranha; Sanya Thaina Cristovam dos Santos; Waldeyde Oderilda Gualberto Magalhães; Adriana Beatriz Silveira Pinto; Shirley Maria de Araújo Passos; Ângela Xavier Monteiro (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to assess the epidemiological profile for dental caries in primary school students in the public education system in Barcelos, as well as to verify its association with the visual acuity assessed. Methods: This is an observational and cross-sectional study of 1,102 students aged 6 to 17 registered in primary school in the public education system. The evaluation of dental caries complies with the method informed by the World Health Organization, on the school patio in natural light and were carried out by a previously calibrated team (Kappa inter-rater from 0.70 to 0.89).  Visual acuity was assessed using the Snellen optometric scale. For the analysis, when the normality hypothesis was accepted by means of the Shapiro-Wilk test, average and standard deviation (SD) were calculated and the parametric tests t-student and Analysis of Variance - ANOVA - were applied. When the normality hypothesis was rejected Mann-Whitney and Kruskal-Waliis non-parametric tests were applied. For the analysis of categorical variables, the Pearson chi-square test was applied. Results: 1,102 students took part in the tests, of whom 556 (50.5%) were male. The prevalence of dental caries found was 72.1% in students aged 6 to 11 and 65.7% in students aged 12 to 17.  The study found an association between Visual Acuity (<0.8) and dental caries in students aged 6 to 11 (p=0.023), and between females and dental caries in students aged 12 to 17 (p=0.025). Conclusion: This study suggests the need for wider oral health coverage in the town of Barcelos in order to provide better access to children and adolescents to restoration treatments so as to prevent the worsening of oral health conditions. Health promotion actions for awareness and the prevention of dental caries must be created taking into account the risk factors found in Barcelos.